Orthogonal Experimental Study on Heat Transfer Optimization of Backfill Slurry with Ice Particles - Mei Wang; Peng Liu; Yuhang Jia; Yujiao Zhao; Bo Zhang (Advances in Civil Engineering)
To reduce the risk of high-temperature geothermal environment in deep mine exploitation, an innovative method for cooling stopes by backfill slurry with ice particles has been focused on. In this paper, aiming at the cooling effect of backfill slurry with ice particles, an experimental device including stope region and ice-filled filling slurry region was established for temperature measurement experimental simulation study. The results showed the ice-filled slurry had a significant cooling effect on the stope region. Orthogonal design experiment and range analysis methods were applied for studying the influencing regularities of four factors, including boundary heat flux, ice-water ratio, sand-cement ratio, and slurry concentration. The effective cooling heat coefficient which is defined by radiation heat flux and boundary heat flux of surrounding rock was applied as an evaluation index for scheme optimization. The influencing rank of the four factors is boundary heat flux >sand-cement ratio >ice-water ratio >slurry concentration. By comprehensive analysis, the optimization of mixture ratio was obtained: the boundary heat flux of the simulated surrounding rocks is 111 W/m2, the ratio of ice to water is 8 : 5, the ratio of sand to cement is 4 : 1, and the slurry concentration is 64%.